POLA KONSUMSI BALITA TERHADAP KEJADIAN STUNTING - Rofiqoh, Rofiqoh; Amanupunnyo, Notesya Astri; Anwar, Rina; Setyowati, Tutik (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: West Golewa sub-district is a sub-district included in the Mangulewa Health Center working area which is at risk of stunting compared to other health centers in Ngada Regency because stunting cases increase every year. The purpose of this study was to determine the consumption patterns of toddlers on the incidence of stunting. The research design used in this study was case control. The study was conducted in the work area of Mangulewa Health Center, West Golewa District. The research was conducted in November 2024. The population is all toddlers in West Golewa District as many as 788 children under five. The sample used a ratio of 1: 1 which amounted to 52 respondents. The sampling technique used in this study was Simple Random Sampling Technique. Data analysis was done univariate and bivariate. The results showed there was a relationship between the number of meals (p value: 0.009) and the type of food (p value: 0.00) to the incidence of stunting. It is recommended that mothers of toddlers be more active in seeking information about balanced nutrition and be more creative in feeding.Keywords: Toddlers, Food, Stunting